Capability of defective graphene-supported Pd13 and Ag13 particles for mercury adsorption - Meeprasert J. (2017)
© 2015 Elsevier B.V. All rights reserved. Reactivity of single-vacancy defective graphene (DG) and DG-supported Pd n and Ag n (n = 1, 13) for mercury (Hg 0 ) adsorption has been studied using density functional theory calculation. The results show that Pd n binds defective site of DG much stronger than the Ag n , while metal nanocluster binds DG stronger than single metal atom. Metal clustering affects the adsorption ability of Pd composite while that of Ag is comparatively less. The binding strength of -8.49 eV was found for Pd 13 binding on DG surface, indicating its high stability. Analyses of structure, energy, partial density of states, and d-band center (ϵ d ) revealed that the adsorbed metal atom or cluster enhances the reactivity of DG toward Hg adsorption. In addition, the Hg adso rption ability of M n -DG composite is found to be related to the ϵ d of the deposited M n , in which the closer ϵ d of M n to the Fermi level correspond to the higher adsorption strength of Hg on M n -DG composite. The order of Hg adsorption strength on M n -DG composite are as follows: Pd 13 (-1.68 eV) > > Ag 13 (-0.67 eV) ∼ Ag 1 (-0.69 eV) > Pd 1 (-0.62 eV). Pd 13 -DG composite is therefore more efficient sorbent for Hg 0 removal in terms of high stability and high adsorption reactivity compared to the Ag 13 . Further design of highly efficient carbon based sorbents should be focused on tailoring the ϵ d of deposited metals.